Factors impacting investors’ intention to invest on peer-to-peer (P2P) lending platform: an extended TAM-based model - Mohd Thas Thaker, Mohamed Asmy; Mohd Thas Thaker, Hassanudin; Rahman, Maya Puspa; Amin, Fouad Md; Allah Pitchay, Anwar; Oladokun, Nafiu Olaniyi (2018)
The Peer to Peer (P2P) lending platform has witnessed a significant growth in recent years, due to advancement of information technology and development of online platforms. Given the importance and popularity of P2P, it is crucial to examine the factors that influence the intentions of investors to invest through P2P lending platform. This study thus proposes and test a model based on extended TAM, to examine factors that influence investors to invest in P2P lending platform. Based on survey questionnaire administered to retail investors from Klang Valley in Malaysia, the results show that intention to invest on P2P platform is mainly influenced or driven by trust. Perceived risk, perceived ease of use and security were found to have no impact on intention to invest on P2P platform. This findings from the present study thus provides managerial implications and theoretical contributions.